A mathematical and didactical analysis of the concept of orientation - Kónya, Eszter (Teaching Mathematics and Computer Science, 2006)
The development of spatial ability, in particular the development of spatial orientation is one of the aims of mathematics education.In my work, I examine the concept of orientation, especially concepts of between, left, right, below, above, front, back, clockwise and anticlockwise. I analyze answers given for a simple orientation task prepared for elementary school pupils. I would like to call attention to the difficulties pupils have even in case of solving simple orientation problems.We have different ways to know more about the crucial points of a concept, especially of the concept of orientation. In this study I bring out one of them. I analyze and make some didactical conclusions about the origin and the axiomatic structure of orientation.